PEMBUATAN APLIKASI LAPORAN KINERJA DOSEN INSTITUT AGAMA ISLAM (IAI) AL-MAWADDAH WARRAHMAH KOLAKA - Chaerunnisa, Saskia; Zakariah, M Askari (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
Lecturer is one of the professions to educate the generation of a nation. The performance of lecturers at universities in Indonesia consists of Educational/Teaching Performance, Research Performance and Community Service Performance. The Microsoft Access application is used to create simple applications Lecturer Performance Report (BKD Dosen) that can be used by the Institut Agama Islam Al Mawaddah Warrahmah Kolaka . Performance improvements can be monitored from applications that are collected, and future performance can be planned.